Corrigendum to âModelling and optimization of photocatalytic degradation of phenol via TiO2 nanoparticles: An insight into response surface methodology and artificial neural networkâ J. Photochem. Photobiol. A: Chem. 384 (2019) 1â15/112039 (Journal of Photochemistry & Photobiology, A: Chemistry (2019) 384, (S1010603019308883), (10.1016/j.jphotochem.2019.112039)) - Zulfiqar, M. (Elsevier B.V., 2020)
The authors regret that the following an extra author should be added into the manuscript. Syed Ali Ammar Taqvi (Department of Chemical Engineering, NED University of Engineering and Technology Karachi, 75270, Karachi). The author has contributed some part in artificial neural network as modelling section. The correct and complete author list should read: Modelling and optimization of photocatalytic degradation of phenol via TiO2 nanoparticles: An insight into response surface methodology and artificial neural network Muhammad Zulfiqar a, Mohamad Fakhrul Ridhwan Samsudin a, Syed Ali Ammar Taqvi c, Suriati Sufian a,b,* aChemical Engineering Department, Universiti Teknologi PETRONAS, 32610 Bandar Seri Iskandar, Perak, Malaysia bCentre of Innovative Nanostructures & Nanodevices (COINN), Universiti Teknologi PETRONAS, 32610 Bandar Seri Iskandar, Perak, Malaysia cDepartment of Chemical Engineering, NED University of Engineering and Technology Karachi, 75270, Pakistan *Corresponding author: suriati@utp.edu.my The authors would like to apologise for any inconvenience caused. Â© 2020